PENGARUH PENGETAHUAN, RISK-RETURN, DAN BANDWAGON EFFECT MEMPENGARUHI MINAT INVESTASI CRYPTOCURRENCY PADA MAHASISWA - Zinedine, Zenedinand; Herwiyanti, Eliada (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2025)
This research examined the influence of knowledge, risk-return, and bandwagon effect on accounting students' cryptocurrency investment interest. The population in this study were active accounting students at Jenderal Soedirman University. The sampling method was purposive sampling. From 277 samples that met the criteria. 122 questionnaires can be used in the next research stage. The results of the study show that investment interest by Generation Z represented by accounting students who have taken financial technology courses is influenced by knowledge, risk-return, and the bandwagon effect. This finding provides evidence that learning about cryptocurrencies makes the younger generation not only have sufficient knowledge but also understand the risk-return of crypto investment instruments which are generally considered to be very uncertain in their performance. Likewise, the bandwagon effect is indeed a common thing among Generation Z to be interested in cryptocurrencies. Although the research results cannot be generalized, it can be concluded that generation Z who have received education about cryptocurrencies already understand the risks behind their investment choices.